Importance and Implications of the Production of Phenolic Secondary Metabolites by Endophytic Fungi: A Mini-Review - Lunardelli Negreiros de Carvalho, Patrícia; de Oliveira Silva, Eliane; Aparecida Chagas-Paula, Daniela; Honorata Hortolan Luiz, Jaine; Ikegaki, Masaharu (Mini Reviews in Medicinal Chemistry, 2016)
In the natural products research, a valuable approach is the prospection of uncommon sources and unexplored habitat. Special attention has been given to endophytic fungi because of their ability to produce new and interesting secondary metabolites, which have several biological applications. The endophytes establish exclusive symbiotic relationships with plants and the metabolic interactions may support the synthesis of some similar valuables compounds. Among secondary metabolites, phenol-derived structures are responsible for several bioactivities such as antioxidant, cytotoxic, antimicrobial, among others. Phenolic compounds might be biosynthesized from the shikimate pathway. Although shikimic acid is a common precursor in plants, it is described as rare in microorganisms. To the best of our knowledge, this is the first review about phenolic compounds produced by endophytic fungi and a comparison has been made with those produced by the plant host. This review covers 124 phenolic secondary metabolites produced by endophytic fungi. Considering the data analyzed by us, only seven of such compounds were isolated from fungi and from their hosts. These observations claim for more attention to phenolic compounds produced by endophytic fungi with a view to understand the real importance of these compounds to endophytes survival.
Keywords: Plant host